Freeze Dried Quetiapine-Nicotinamide Binary Solid Dispersions: A New Strategy for Improving Physicochemical Properties and Ex Vivo Diffusion. (30th November 2016) - Ali, Ahmed Mahmoud Abdelhaleem; Al-Remawi, Mayyas Mohammad Ahmad
Abstract : Improving the physicochemical properties and oral bioavailability of quetiapine fumarate (QF) enabling enhanced antipsychotic attributes are the main aims of this research. The freeze dried solid dispersion strategy was adopted using nicotinamide (NIC) as highly soluble coformer. The prepared dispersions were characterized using scanning electron microscopy (SEM) differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Static disc intrinsic dissolution rate and ex vivo diffusion through intestinal tissues were conducted and compared to pure quetiapine fumarate. The results demonstrated a highly soluble coamorphous system formed between quetiapine fumarate and nicotinamide at 1 : 3 molar ratio through H-bonding interactions. The results showed >14-fold increase in solubility of QF from the prepared dispersions. Increased intrinsic dissolution rate (from 0.28 to 0.603 mg cm −2 min −1 ) and faster flux rate through duodenum (from 0.027 to 0.041 mg cm −2 h −1 ) and jejunum (0.027 to 0.036 mg cm −2 h −1 ) were obtained. The prepared coamorphous dispersion proved to be effective in improving the drug solubility and dissolution rate and ex vivo diffusion. Therefore, binary coamorphous dispersions could be a promising solution to modify the physicochemical properties, raise oral bioavailability, and change the biopharmaceutics classification (BCS) of some active pharmaceutical ingredients.